The community college student perception about classroom factors that affect learning - Veltri, Sandra K., author; Banning, James H., advisor; Davies, Timothy G., advisor; Lehmann, Jean P., committee member; Clemons, Stephanie A., committee member (Colorado State University. Libraries, 2003)
Historically the classroom has taken on many forms and meanings to various individuals. The evolution of the classroom has progressed from the crude campfires of cavemen and nomads to the technologically advanced spaces for learning of today. Those who fund education and other stakeholders are now investigating the relationship of the built environment to the learner. This study investigates how the physical factors of a community college classroom affect a student's learning. A brief review of the history of the community college provides a context for this study. An overview of buildings in relationship to behavior is also presented. The conceptual framework of brain-based learning is discussed as a connector between the physical classroom environment and learning. This is a qualitative multiple case study that uses focus groups, wish drawings, and archival data to investigate the value placed on the learning environment by a chosen community college and perceptions of students interacting within those environments to identify factors that they identify as a contribution and/or hindrance to their learning.
Keywords: community colleges; educational psychology; community college education